EXPLORATION OF STRATEGIC FACTORS THAT INFLUENCE KEDAI UMAH PRADJA PERFORMANCE BASED ON IFE AND EFE ANALYSIS - Mesiana, Tirza; Padang, Rikky Rundu (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to explore the strategic factors that influence the performance of Kedai Umah Pradja, a culture-based culinary MSME in Singaraja, Bali. The novelty of this study lies in the application of IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) analysis to businesses that integrate local cultural identity into their business strategies. Using a descriptive quantitative approach, data were obtained through questionnaires administered to four internal staff members and field observations. The results showed an IFE score of 4.74 and an EFE score of 4.53, placing Kedai Umah Pradja in the Strength–Opportunity (SO) quadrant, which is suitable for implementing an aggressive strategy. The main strategies proposed include local culture-based product innovation, digitization of promotion and services, and partnerships with local suppliers. This study contributes theoretically by linking cultural identity and structured strategic analysis, and provides practical implications for similar MSMEs in designing sustainable business strategies.